The Quality of Aesthetic Development in The Context of An Art Festival as A Condition for The Overall Development of Children and Adolescents - Boyakova, Ekaterina V. (2020)
The article examines the problem of the aesthetic development of children and adolescents as a fundamental condition for the quality of education and the modern approach to educational process organization in the context of interaction of general and additional education. The authors disclose this direction of research from the point of a long-term experimental study conducted by researchers at the Institute of Art Education and Cultural Studies of the Russian Academy of Education in the period from the middle of the 20th and the beginning of the 21st century. The analysis of materials of a substantial scientific study of the problem of measuring the aesthetic development of children on the example of Russia and the studies by the leading foreign scientists is carried out. The authors raise the issues related to solving this problem in modern educational organizations and schools. The article identifies the modern pedagogical principles and conditions for the implementation of the basics of aesthetic development including the aesthetic perception of the works of art by children of different ages in the practice of children’s educational organizations. The resolution of the problem of high-quality modern education is found in creating a well-organized subject and spatial environment, changing all the components of education and upbringing, and highlighting the fundamental cultural core in them.